Global models for concrete realities (Cadernos de Sociomuseologia, 2010)
This paper intends to analyze the evolution of the Ecomuseums from their early appearance in the seventies until the present, emphasizing the characteristics which make them unique and different  from all the other museums. This analysis will be used to show the Japanese landscape on ecomuseums and how the ecomuseum evolution might be a reference at internatioal level.